2012
DOI: 10.1093/cvr/cvs137
|View full text |Cite
|
Sign up to set email alerts
|

Non-endothelial cell endothelin-B receptors limit neointima formation following vascular injury

Abstract: These results are consistent with ETB receptor activation playing an important role in limiting neointimal lesion formation following acute vascular injury, but indicate that this protective effect is not mediated by those ETB receptors expressed by endothelial cells. These data support the proposal that selective ETA antagonists may be preferable to mixed ETA/ETB antagonists for targeting the arterial response to injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…Mice were injected intraperitoneally with saline or increasing concentrations of PAG from E8.5, and blood pressure was measured by tail-cuff plethysmography. 29 In addition, arterial blood pressure was also measured in pregnant mice at E17.5 as described previously 30 for GYY4137 studies. In brief, mice were anesthetized by using a ketamine/ xylazine cocktail, and the carotid artery was isolated and cannulated with a Millar 1-French Mikro-Tip pressure catheter connected to a pressure transducer (ADInstruments Ltd, Oxford, UK).…”
Section: Animal Experimental Protocolmentioning
confidence: 99%
“…Mice were injected intraperitoneally with saline or increasing concentrations of PAG from E8.5, and blood pressure was measured by tail-cuff plethysmography. 29 In addition, arterial blood pressure was also measured in pregnant mice at E17.5 as described previously 30 for GYY4137 studies. In brief, mice were anesthetized by using a ketamine/ xylazine cocktail, and the carotid artery was isolated and cannulated with a Millar 1-French Mikro-Tip pressure catheter connected to a pressure transducer (ADInstruments Ltd, Oxford, UK).…”
Section: Animal Experimental Protocolmentioning
confidence: 99%
“…Kirkby et al [26] demonstrated that nonendothelial cell ET B receptors could limit the development of neointimal formation after wire injury using endothelial cell-specific ET B knockout mice. That is, selective deletion of ET B receptors from the endothelium had no effect on neointimal formation after vascular injury whereas a selective ET B receptor antagonist aggravated neointimal formation after vascular injury in mice [26]. Furthermore, they showed that a selective ET B receptor antagonist reversed the vasoprotective effects of a selective ET A receptor antagonist in the same model [26].…”
Section: Pathophysiological Roles Of the Etb Receptor In Vascular mentioning
confidence: 99%
“…That is, selective deletion of ET B receptors from the endothelium had no effect on neointimal formation after vascular injury whereas a selective ET B receptor antagonist aggravated neointimal formation after vascular injury in mice [26]. Furthermore, they showed that a selective ET B receptor antagonist reversed the vasoprotective effects of a selective ET A receptor antagonist in the same model [26]. These findings indicate that nonendothelial ET B receptors have aggressive vasoprotective effects and that selective ET A receptor antagonists are preferable to ET A /ET B receptor antagonists for the treatment of vascular injury.…”
Section: Pathophysiological Roles Of the Etb Receptor In Vascular mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed we have now used OPT to demonstrate the effect of pharmacological interventions and genetic manipulation on atherosclerotic and neointimal lesion size. For example, endothelin receptor blockade altered neointimal lesion formation whereas selective deletion of the endothelin B receptor from the vascular endothelium did not 15 . In atherosclerosis prone mice, genetic deletion of the enzymes 11β-HSD1 16 or galectin 3 17 were shown to reduce the size of atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%